2004
DOI: 10.1063/1.1642580
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and classical studies of the O(3P)+H2(v=0–3,j=0)→OH+H reaction using benchmark potential surfaces

Abstract: We present results of time-dependent quantum mechanics (TDQM) and quasiclassical trajectory (QCT) studies of the excitation function for O(3P) + H2(v = 0-3,j = 0) --> OH + H from threshold to 30 kcal/mol collision energy using benchmark potential energy surfaces [Rogers et al., J. Phys. Chem. A 104, 2308 (2000)]. For H2(v = 0) there is excellent agreement between quantum and classical results. The TDQM results show that the reactive threshold drops from 10 kcal/mol for v = 0 to 6 for v = 1, 5 for v = 2 and 4 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 28 publications
14
44
0
Order By: Relevance
“…The roles of the singlet-triplet transitions are negligible for branch ratios below 5%, and among these insignificant transitions, the transition between 1 AЈ and 3 AЉ͑2͒, 1 AЈ and 3 AЉ͑1͒, and 1 AЈ and 3 AЈ contributes to the singlet-triplet intersystem crossing in a descending order. However, if we statistically average the fine-structure resolved cross sections in the O͑ 3 P 2,1,0 ͒ +H 2 reaction, we could see that the effects of the spin-orbit coupling on the total reaction cross sections are insignificant, which agrees with the recent studies of Braunstein et al 20 and Balakrishnan. 21 Figure 5 shows the product ratio of the OH spin state ⌸ 3/2 to ⌸ 1/2 for the wave packet initially on the triplet surfaces.…”
Section: -3supporting
confidence: 79%
See 1 more Smart Citation
“…The roles of the singlet-triplet transitions are negligible for branch ratios below 5%, and among these insignificant transitions, the transition between 1 AЈ and 3 AЉ͑2͒, 1 AЈ and 3 AЉ͑1͒, and 1 AЈ and 3 AЈ contributes to the singlet-triplet intersystem crossing in a descending order. However, if we statistically average the fine-structure resolved cross sections in the O͑ 3 P 2,1,0 ͒ +H 2 reaction, we could see that the effects of the spin-orbit coupling on the total reaction cross sections are insignificant, which agrees with the recent studies of Braunstein et al 20 and Balakrishnan. 21 Figure 5 shows the product ratio of the OH spin state ⌸ 3/2 to ⌸ 1/2 for the wave packet initially on the triplet surfaces.…”
Section: -3supporting
confidence: 79%
“…We should mention here that Braunstein et al 20 and Balakrishnan 21 have reported their nonadiabatic dynamics calculations on the O͑ 3 P͒ +H 2 reaction very recently, and the agreement between these calculated total reaction cross sections and the experimental results tends to indicate the insignificance of the spin-orbit effects in this reaction. However, the present study differs apparently from the above investigations partly in that the problem of interest is not the spinorbit effects on the total reaction cross sections but on the fine-structure resolved reaction cross sections.…”
Section: Introductionmentioning
confidence: 97%
“…This is sufficient to obtain converged cross sections for kinetic energies up to 0.25 eV. Figure 2 compares cross sections for the 3 A" surface obtained from the exact calculations with those obtained from the J-shifting approximation, the quantum mechanical and QCT results of Braunstein et al [2004], and the QCT results of Johnson and Winter [1977]. The PES employed by Braunstein et al [2004] is the same as that used in the present study.…”
Section: Resultsmentioning
confidence: 92%
“…The PES employed by Braunstein et al [2004] is the same as that used in the present study. It is seen that J-shifting approximation works extremely well for this system and that our results agree quantitatively with the quantum mechanical results of Braunstein et al [2004]. The QCT results, agree with each other, but depart significantly from the quantum results at low energies.…”
Section: Resultsmentioning
confidence: 99%
“…7 Maiti and Schatz have used TSH to study spin-orbit interaction induced intersystem crossing effects in the O + H 2 reaction, including four PESs in this model. 8 This reactive system has been thoroughly investigated both experimentally and theoretically, [9][10][11][12] although the first quantum wave-packet study involving four coupled electronic surfaces has been reported only recently. 13 Accurate PESs are available due to Rogers et al 14 and Dobbyn and Knowles, 15 and the spin-orbit couplings have been determined by Hoffmann and Schatz.…”
Section: Introductionmentioning
confidence: 99%